Micromammals and the Holocene environment of Mzinyashana Shelter 1 - Avery, D. M. (Southern African Humanities, 2021)
The Mzinyashana 1 micromammalian sample provides information on environmental conditions in the northern Thukela catchment area during the period from about 4100 to 660 b.p. The common molerat Cryptomys hottentotus is the dominant species in all layers, except those dated to about 2840 b.p. and 660 b.p., when it was replaced by the vlei rat Otomys irroratus. The evidence suggests an overall deterioration in conditions from about 4000 to 900 b.p. coinciding with the interval between the mid-Holocene climatic optimum and the onset of the Little Ice Age. Mean annual rainfall was probably relatively high around 1900 b.p., when vegetation was most bushy. At other times, rainfall seasonality may have been enhanced without there necessarily being an overall increase. Vegetation was predominantly grassland throughout. To cite this paper: Avery, D.M. 1997. Micromammals and the Holocene environment of Mzinyashana Shelter 1. Natal Museum Journal of Humanities 9: 37-46.